Raven tales. Baby blues [videorecording (DVD)] - Moore, Carmen (Indigenous Collection., 2017)
Widi's new baby sister only stops crying if she has Widi's warrior doll, but Widi runs away with it. Frog finds him and tells him a story about sacrifice.